Coronary Artery Disease in patients with End‐Stage Kidney Disease; Current perspective and gaps of knowledge. Issue 3 (25th May 2020) - Levi, Amos; Simard, Trevor; Glover, Christopher
Abstract: Coronary artery disease (CAD) is very common in dialysis patients. One third have preexisting CAD and another one third have significant occult disease at the time of starting dialysis. Symptoms are often absent or are atypical, emphasizing the need for vigorous screening, specifically in patients awaiting transplant. The lesions tend to be heavily calcified, diffuse, and involve multiple vessels, consequently, percutaneous coronary interventions are more complicated to perform, and are less successful in achieving and maintaining short‐ and long‐term patency. Dialysis patients have been excluded from the randomized controlled trials on which the current standards for managing CAD have been established. Due to differences in pathobiology and risks and benefits, it is uncertain that the results of these clinical trials extrapolate to patients with advanced chronic kidney disease (CKD). Here we review the data from observational studies and identify special considerations concerning the diagnosis and management of CAD in dialysis patients, including the use of noninvasive functional testing vs anatomical testing, the management of acute coronary syndromes and of stable coronary artery disease, the role for percutaneous revascularization vs coronary artery bypass grafting, and of platelet inhibitor therapy after coronary stenting. We review the preliminary results of the recently published ISCHEMIA‐CKD trial, the only trial to date to involve large numbers of dialysis patients. This is the first of, hopefully, many trials in the pipeline that will examine therapies for CAD specifically in patients with advanced CKD, a growing population that is at particularly high risk for poor outcomes.